ANALYSIS OF TOXIC DISINHIBITION IN TEACHER - Risda Heldriyana; Afdal (RADJA PUBLIKA, 2023)
This study aims to look at the description of toxic disinhibition behavior, as well as see the relationship between each aspect of toxic disinhibition behavior among teachers who live in rural, urban and urban areas. A total of 386 teachers consisting of 105 males and 281 females were taken as samples in this study using incidental sampling techniques. Data was collected using a toxic disinhibition questionnaire to measure the behavior of toxic disinhibition based on the six aspects, namely dissociative anonymity or anonymity, invisibility, asschornicity, solipsistic interjection, dissociative imagination, minimizatioano Itas, namely construct validity and content validity, the instruments used are 21 items and reliable values ​​with a value of 0.824. The data were analyzed descriptively by correlation and the results were obtained that toxic disinhibition behavior among teachers was in the medium category with a proportion of 74% and for the low category it was in the presentation of 24% and in the high category it was in the presentation of 2%, but in every aspect of toxic disinhibition not all aspects are interconnected with one another, but most are interconnected, especially in the Dissociative imagination aspect there is no relationship with other aspects. , everyone has a different toxic disinhibition behavior in every aspect. but in every aspect of toxic disinhibition not all aspects are interconnected with one another, but most are interconnected, especially in the Dissociative imagination aspect there is no relationship with other aspects. , everyone has a different toxic disinhibition behavior in every aspect. but in every aspect of toxic disinhibition not all aspects are interconnected with one another, but most are interconnected, especially in the Dissociative imagination aspect there is no relationship with other aspects. , everyone has a different toxic disinhibition behavior in every aspect.